Boto cinza (Sotalia guianensis, Van Benédén, 1864) (Cetacea, Delphinidae): Atividade aérea, forrageio e interações inter-específicas, na Praia de Pipa (Tibau do Sul RN) e estudo comparativo entre duas populações do Nordeste do Brasil - Nascimento, Lídio França do (2006)
Sotalia guianensis is a small cetacean of the Delphinidae family, with coastal habits and whose area of distribution ranges from Florianópolis (27º35'S, 48º34'W), in Brazil, to Honduras (15º58'N, 85º42'W). At Pipa beach, on the south coast of RN state, in Brazil, the species occur throughout the year. The present study was carried out in two bays, which are bordered by cliffs. The animals were monitored from vantage points, using the "Ad libitum" and "all the occurrences" methods; during the years of 1999 and 2004. The study was divided in 4 chapters: Behavioral standards of two populations of gray dolphin, (Sotalia guianensis, Van Benédén, 1864) in the northeast of Brazil; Aerial activity of the gray dolphin: its possible function and the influence of environmental and behavioral factors; The influence of daily and monthly variation of the tides, of the period of the day and group size on the gray dolphin forage activity; kleptoparasitism interactions of frigatebird (Fregata magnificens, Mattheus, 1914) during the gray dolphin forage activity. The results have shown that the gray dolphin has a varied and complex behavioral repertoire. The leap is the most frequent behavior; the aerial activity is diffuse during daylight and is influenced by some factors, such as the level of the tide and social factors. The gray dolphin, when in the bay, most frequently feeds isolate or in small groups. The forage is diffuse during daylight; however, being more frequent in the morning and is influenced by the daily and monthly variation of the tide. At Pipa beach, kleptoparasitarian interactions were registered between the gray dolphin and the frigatebird (Fregata magnificens). The frigatebird forage strategy consists basically of two ways: to fly over great extensions searching for dead fish and to steal food (kleptoparasitism). These interactions were predominantly carried out between immature and female adult birds and adult and immature dolphins, and occurred during daylight. The present study can be considered an initial landmark to a better knowledge on the gray dolphin surface behavior, especially regarding the aerial behavioral repertoire and forage strategy of this species. However, it is necessary to continue these studies, so that we can understand better the complex social life of these animals and thus create effective measures for its conservation